Poúrazová korekcní osteotomie distálního radia s novou dlahou - Cizmár, I; Wendsche, P; Brychta, P; Visna, P; Mensík, I (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2002)
PURPOSE OF THE STUDY: Mal-union of distal radius fractures cause functional limitation and progressive degenerative changes of the wrist. The authors evaluate both radiograph and functional outcomes in a group of patients with a post-traumatic deformation of the distal radius treated by corrective osteotomy and fixation by a newly developed T-plate. MATERIAL: A retrospective evaluation covered a group of 13 patients of the average age of 51 years (range, 35-60 years) operated on in 2001 for post-trauma symptomatic mal-union of the distal radius of the Colles type. The group included only patients in which a new implant was used. The time interval between the primary fracture and corrective osteotomy was on average 11 months. METHODS: Corrective osteotomy for Colles deformations was performed in all patients from the dorsal approach with the application of a cortico-cancellous bone graft. Stabilisation was performed by the mentioned plate. Radiograph and functional outcomes were evaluated statistically. RESULTS: The radiographic evaluation proved the restoration of the normal anatomic relationship between the distal radius and ulna as well as statistically significant improvement of the function of the hand as concerns the range of motion and muscular strength Except for one patient, all involved evaluated the outcome as a subjective improvement. DISCUSSION: Corrective osteotomy of the distal radius is a standard surgery performed routinely by plate fixation with the application of a cortico-cancellous bone graft. Despite a perfect coverage of the issues relating to potential consequences resulting from non-anatomic position of the articular surface of the distal radius, this surgery was not very frequent in the past. Nevertheless, recently, there is a growing number of works in the literature dealing with corrective osteotomies for mal-union of the distal radius after fractures not only for the Colles but also Smith type. CONCLUSIONS: Treatment of deformation of the distal radius is a rewarding procedure which brings the patients a significant improvement of the function of the hand. The implant used by the authors proved useful for a plate fixation on the distal radius.
Keywords: Radius; Fractures, Malunited; Humans; lidé středního věku; osteotomie; Female; dospělí; radius; fraktury vřetenní kosti; lidé; Adult; Radius Fractures; ženské pohlaví; Bone Plates; kostní destičky; Male; Middle Aged; špatně zhojené fraktury; mužské pohlaví; Osteotomy